Dietary Acculturation of Obesity Risk Reduction Behaviors in Chinese Americans. (1st December 2018) - Liou, Doreen; Bauer, Kathleen D.; Fowler, Emily
Abstract : Increasing rates of obesity among successive generations occur among Chinese Americans. This cross‐sectional survey measured obesity risk reduction behaviors and degree of acculturation among a convenience sample of 203 Chinese Americans living in Los Angeles, California. Asian‐identified participants were most likely to follow traditional healthful Chinese food patterns, and Western‐identified individuals were more apt to engage in leisure physical activity. Individuals categorized as bicultural were prone to use limited amounts of fats or oils when preparing foods. Health professionals and educators working with Chinese Americans need to consider the impact of acculturation affecting the adoption of obesity prevention behaviors.